Synthesis of Novel Suramin Analogs With Anti-Proliferative Activity via FGF1 and FGFRD2 Blockade - Parveen, Nuzhat; Lin, Yan-Liang; Chou, Ruey-Hwang; Sun, Chung-Ming; Yu, Chin (Frontiers in Chemistry, 2022)
One of the promising approaches in cancer therapy is the inhibition of cell proliferation by using small molecules. In this study, we report the derivative synthesis of the suramin compounds and their applications. We used the NMR spectroscopy, docking simulations to confirm the binding site and 3D model of the ligand-protein complex. WST1-assay was used for cell viability and cell proliferation to study the inhibition of protein-protein interaction and to investigate the anti-proliferation activities in a breast cancer cell line. All the suramin derivatives showed anti-proliferant activity by displaying a blockade between FGF1 and FGFRD2, dissociation constant was measured by the fluorescence spectroscopy. These derivatives of suramin compounds could be used in a novel therapeutic approach for anti-proliferation by the inhibition of protein-protein interaction. The cytotoxicity of these suramin derivatives was found lower than that of the suramin, which can be considered as advanced progress in this field. Thus, these compounds could be considered as better anti-metastasis molecules than suramin.